Toadas de Bumba meu boi: um canto entre a palavra folclórica e a voz poética - Serejo, Janick de Lisieux Diniz (2017)
According to the version of Bueno (1999), the legend of St. John's little ox is recreated by the Bumba meu boi Maranhense through oral tradition, so common during the presentations of jokes and exaltations to St. Anthony, St. John, St. Peter and São Marçal, the latter two being much revered by the groups considered as root accents (matraca and zabumba). In this dissertation, we deal with the plays of Bumba meu boi, with the purpose of recognizing in the oral performance aspects of the poetics present in the construction of the formal and erudite culture of Maranhão. The objective is to investigate the toadas as a magical element of construction of the popular vernacular as a poetic voice. The corpus selects five toadas for the analysis of orality, whose choice is due to the representativeness of the folk groups, duly proven by the large number of followers during popular rehearsals and presentations. In the adopted methodology there are three stages: 1) the bibliographic cataloging to favor a better understanding of the regional research; 2) the visit to the barracks and test sites; 3) the presence and oral recording of the presentations of the groups of singers, with the purpose of selecting the corpus of analysis and reading. Based on the conception of the ethnologist Paul Zumthor that oral poetry is present in the most varied artistic manifestations that have the voice as the raw material for singing, we aim to prove that faith and devotion to the sacred offer composers, Or Amos of Bumba meu boi, structural elements to describe the poetic in the magic of toadas